Optimasi Penentuan Basis Risiko pada Jaringan Saham Keuangan Menggunakan Dimensi Metrik untuk Estimasi Value at Risk - Annisa Hevita Gustina Kumalasari Saefulloh; Putri Isnaini Cahyaning Baiti; Erica Grace Simanjuntak; Rahmatika Zaqiatul Latifah (Universitas Negeri Gorontalo, 2026)
This study aims to optimize systemic risk monitoring in the Indonesian financial sector network by determining the minimum risk basis using the Metric Dimension concept. The high complexity of inter-asset correlations requires a dimension reduction method that maintains structural information regarding risk exposure. Daily stock price data from 10 financial issuers (banking, insurance, and financing) for the five-year period from January 1, 2021, to December 31, 2025, were used. The data were transformed into a weighted graph through a log-return correlation matrix converted into metric distances. The resolving set (W) was determined using a greedy algorithm to identify the optimal basis. Validation was performed by analyzing the correlation between the metric coordinates of each issuer and its 95% Value at Risk (VaR). The results showed that the financial network has a metric dimension of dim(G) = 1, with ADMF.JK selected as the optimal resolving set (basis). Actuarial validation revealed a significant negative correlation (−0.5495) between the metric distance and VaR. This implies that the metric distance from the basis can linearly map the magnitude of market risk, offering an efficient strategy for investment managers to monitor portfolio stability through a single reference entity.